ADVANCES IN THE UNDERSTANDING OF NEOGENE MAMMALIAN FAUNA IN THE PAMPEAN REGION (CENTRAL ARGENTINA) THROUGH REVISING “BIOZONE” HYPOTHESES BASED ON NEW DATES AND BIOCHRONOLOGICAL ANALYSES (Ameghiniana, 2023)
Fossil vertebrates, especially mammals, of the Neogene–Quaternary of Central Argentina were fundamental to the construction of time and rock-time scales and the knowledge of the biotic evolution of southern South America. The poverty of fossiliferous localities constrained with radiometric and/or paleomagnetic data heavily complicated the correlation of different faunas and their temporal allocation. The Cerro Azul Formation (Argentina) constitutes a suitable example of this situation but also enlarged because its fossils have been collected from scattered and isolated small outcrops whose chronological ordering was based on the “stage of evolution” of some rodents. We present here new dates for the fauna/locality of Telén (La Pampa Province) plus extensive biochronological analyses covering 16 fossiliferous localities referred to Cerro Azul Formation. Two dates from an “escoria” sample gave 7.09 Ma for Telén assemblage, an age in accordance with that obtained from an independent faunal analysis. Faunal ordination and age obtained with regression analyses identify a succession of faunas/localities that cover the time range between 8–5.33 Ma. The older assemblages (e.g., Cerro Bota) appear to be transitional between Chasicoan and “Huayquerian” faunas. The first records of procyonids and cricetid rodents, two North American lineages, are not synchronic (7 and 5.7 Ma, respectively). Our results show important temporal overlapping among the proposed successive rodent ”biozones”. The use of the “stage of evolution” in the analyses does not improve the results, suggesting that its application without independent chronological/ biostratigraphical constraints is not appropriate.